QuantiFERON-TB Gold In-Tube as a Confirmatory Test for Tuberculin Skin Test in Tuberculosis Contact Tracing: A Noninferiority Clinical Trial. (18th August 2017) - Muñoz, Laura; Santin, Miguel; Alcaide, Fernando; Ruíz-Serrano, Maria Jesús; Gijón, Paloma; Bermúdez, Elena; Domínguez-Castellano, Angel; Navarro, María Dolores; Ramírez, Encarnación; Pérez-Escolano, Elvira; López-Prieto, María Dolores; Gutiérrez-Rodriguez, José; et al.
Abstract : This is the first clinical trial comparing 2 diagnostic strategies, with and without an interferon-gamma release assay, for targeting preventive therapy in tuberculosis contact investigations. Confirming positive tuberculin skin test results with QuantiFERON-TB Gold In-Tube significantly and safely reduces the proportion of unnecessary preventive treatments. Abstract: Background: Screening strategies based on interferon-γ release assays in tuberculosis contact tracing may reduce the need for preventive therapy without increasing subsequent active disease. Methods: We conducted an open-label, randomized trial to test the noninferiority of a 2-step strategy with the tuberculin skin test (TST) followed by QuantiFERON-TB Gold In-Tube (QFT-GIT) as a confirmatory test (the TST/QFT arm) to the standard TST-alone strategy (TST arm) for targeting preventive therapy in household contacts of patients with tuberculosis. Participants were followed for 24 months after randomization. The primary endpoint was the development of tuberculosis, with a noninferiority margin of 1.5 percentage points. Results: A total of 871 contacts were randomized. Four contacts in the TST arm and 2 in the TST/QFT arm developed tuberculosis. In the modified intention-to-treat analysis, this accounted for 0.99% in the TST arm and 0.51% in the TST/QFT arm (−0.48% difference; 97.5% confidence interval [CI], −1.86% to 0.90%); in the per-protocol analysis, the corresponding rates were 1.67% and 0.82% in the TST and TST/QFT arms, respectively (−0.85% difference; 97.5% CI, −3.14% to 1.43%). Of the 792 contacts analyzed, 65.3% in the TST arm and 42.2% in the TST/QFT arm were diagnosed with tuberculosis infection (23.1% difference; 95% CI, 16.4% to 30.0%). Conclusions: In low-incidence settings, screening household contacts with the TST and using QFT-GIT as a confirmatory test is not inferior to TST-alone for preventing active tuberculosis, allowing a safe reduction of preventive treatments. Clinical Trials Registration: NCT01223534.